Synthesis and antimicrobial activities of pyrido[2,3-d]pyrimidine, pyridotriazolopyrimidine, triazolopyrimidine, and pyrido[2,3-d:6,5d’]dipyrimidine derivatives - Abdel-Aziem, Anhar; El-Gendy, Marwa Sayed; Abdelhamid, Abdou Osman (European Journal of Chemistry, 2012)
A new series of pyridotriazolopyrimidines were synthesized via reaction of hydrazonoyl halides with pyrido[2,3-d]pyrimidines. The structures of the newly synthesized compounds were established by elemental analysis, spectral data and alternative synthetic routes whenever possible. Some of synthesized compounds were also screened in vitro for their antimicrobial activity against a variety of bacterial and fungal samples.